GAMBARAN BUDAYA KESELAMATAN PASIEN DI RUANG RAWAT INAP MENGGUNAKAN METODE STUDY LITERATURE REVIEW - Indriyani Saputri (Nusantara Hasana Journal, 2022)
Patient safety is an important component of health quality. Even with continuous surveillance, as a health care provider is faced by many challenges in the health care area in an effort to always keep patients safe and awake. The goal of the study was to analyze several journals related to the cultural picture of patient safety in hospital inpatient rooms. This research uses literature review research design or literature review literature review literature literature review. With the number of journals as many as 35 research journals that have been published from 2016-2021. Of the 35 journals that have been found 8 journals with bad categories, 5 journals with moderate categories, 22 journals with good categories The results of this study's patient safety culture are strongly linked to incidents of patient safety incidents. With the increasing culture of patient safety, the incidence of patient safety incidents will be minimized. Important aspects that must be implemented, namely the aspect of communication with good communication between patients and medical personnel will have a positive impact such as minimizing misunderstandings and ethical aspects are very important about carrying out nursing care procedures in health services, medical personnel must be in accordance with the code of ethics and health law to avoid malpractice. It is expected that hospitals can maintain or provide training to nurses then patient safety knowledge will increase, and nurses will be more competent.